Bringing CASE in from the cold: the teaching and learning of thinking - Oliver, Mary; Venville, Grady (Springer, 2016)
Thinking Science is a two-year program of professional development for teachers and thinking lessons for students in junior high school science classes. This paper presents research on the effects of Thinking Science on students’ levels of cognition in Australia. The research is timely with a general capability focused on critical thinking in the newly implemented F-10 curriculum in Australia. The design of the research was a quasi-experiment with pre and post-intervention cognitive tests conducted with participating students (n = 655) from nine cohorts in seven high schools. Findings showed significant cognitive gains compared with an age matched control group over the length of the program. Noteworthy, is a correlation between baseline cognitive score and school Index of Community Socio-Educational Advantage (ICSEA). We argue that the teaching of thinking be brought into the mainstream arena of educational discourse and the principles from evidence-based programs such as Thinking Science be universally adopted.